Effects of Mechanical Alloying on Ni-Rich NiTi Shape Memory Alloys Produced by Hot Isostatic Pressing - Zeybek, Umit; Karaoglu, Serdar (Allerton Press, 2022)
Although Ni-rich 60 NiTi shape memory alloy (SMA) shows superior properties, it is difficult to process due to its high hardness and studies on the manufacturing method are still needed. By the hot isostatic pressing process (HIP), parts close to the net shape are produced and the second operation may no longer be required. In this study, the effects of mechanical alloying on NiTi alloy produced by the HIP process were investigated. The starting powders of the first group were mechanically alloyed. The starting powders of the second group were mechanically mixed. Afterwards, the microstructures, transformation temperatures and some mechanical properties of these two groups were compared. For these examinations, SEM-EDS, XRD, DSC analyzes and microhardness measurement, density measurement by hydrostatic weighing method were performed. The result showed, mechanical alloying causes a more homogeneous microstructure and higher transformation temperatures.

This study was financially supported by Ege University (FDK-2019-20798 doctoral scientific research project) and Kastamonu University (Project no: KUhzdes2021/47).

Ege University [FDK-2019-20798]; Kastamonu University [KUhzdes2021/47]
Keywords: Tini; shape memory alloy; R-Phase; Phase-Transformation Behavior; transformation temperature; hot isostatic pressing; NiTi; mechanical alloying; Martensitic-Transformation; Powders; Microstructure